Marketing Strategy Through Halal Product Advertisements On Social Media - Handayani, Nur Annisa Tri; Nuralim, Aip; Zen, Muhamad; Fatmawati (Institut Agama Islam Negeri Parepare, 2024)
This research aims to find out the marketing strategy for halal products through social media. This research is a literature study. The collected data will be analyzed using a literature review. The research results show that marketing strategies are directed at increasing the likelihood or frequency of consumer behavior, such as increasing visits to certain stores or purchasing certain products. Effective and efficient product advertising via social media. The importance of the halal label in product advertising can be very significant, especially in the context of markets that have a large Muslim population. The halal label not only reflects compliance with religious principles, but can also be a key factor in building consumer trust and expanding market share for producers.